Applicability of force majeure clause in construction contract in Malaysia - Sofiah Abdollah, 1986-; Norazam Othman, supervisor; Fakulti Alam Bina (2010)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2010